Migration decisions and climate change adaptation : synthesis findings from the Upper Indus Basin and semi-arid plains in Pakistan - Ishfaq, Sadia Munawar; Saeed, Basharat Ahmed (2018)
This Synthesis Paper is supported by the Opportunities and Synergy Fund of the Collaborative Adaptation Research Initiative in Africa and Asia (CARIAA). The field studies that form the basis of this paper were carried out by two consortia – Pathways for Resilience in Semi-arid Economies (PRISE) and Himalayan Adaptation, Water and Resilience (HI-AWARE) Research on Glacier and Snowpack Dependent River Basins for Improving Livelihoods. CARIAA is financially supported by the UK Government’s Department for International Development (DFID) and the International Development Research Centre, Canada. Climate change is likely to affect human mobility patterns, particularly, in resource-dependent rural areas where livelihoods and economic activities are climate-sensitive. This is especially true for a country like Pakistan which has a large rural population dependent on agriculture, livestock and forestry for its livelihoods. Over the past decades, changing rainfall patterns and temperature fluctuations across the country have increased difficulties for those engaged in agriculture and other sources of rural livelihoods. Poverty, food insecurity, low human development, poor governance and inadequate access to health and education services have exacerbated rural vulnerability which has led to the need for rural livelihood diversification. As a consequence, a proportion of the rural population has adapted by shifting livelihoods away from the agriculture sector, and in some cases, moving to urban areas altogether. While there are limited studies in Pakistan on the phenomenon of rural-to-urban migration in response to climate change, this synthesis paper is an attempt at filling the literature gap on migration as an adaptation strategy in rural communities vulnerable to climatic impacts and risks.